The Antarctic ozone hole during 2012 - Andrew Klekociuk; Tully, MB; Krummel, PB; Gies, HP; Simon Alexander; Fraser, PJ; Henderson, SI; Javorniczky, J; Petelina, SV; Shanklin, JD; Schofield, R; Stone, KA (2014)
We review the 2012 Antarctic ozone hole, making use of various meteorological reanalyses, remotely sensed ozone measurements and ground-based measurements of ultra-violet radiation. Based on analysis of 33 years of satellite records, we find that the ozone hole of 2012 was one of the least severe since the late 1980s in terms of maximum area, minimum ozone level and total ozone deficit. In particular, the estimated integrated ozone mass effectively depleted within the ozone hole of 2012 was approximately 720 Mt, which is the 12th smallest deficit on record and 28 per cent of the peak deficit observed in 2006. The key factor in limiting the extent of Antarctic ozone loss in 2012 was the relatively warm temperatures that occurred in the Antarctic stratosphere from early July. These warm temperatures, which were driven by dynamical activity, limited the activation of ozone depletion chemistry within the polar vortex during the latter part of the polar winter. Additionally, dynamical disturbances to the polar cap region during spring were aided by the prevailing phase of the Quasi-Biennial Oscillation (QBO) which was strongly negative (westward) and favouring the poleward propagation of heat flux anomalies; these disturbances resulted in the steady erosion of the vortex and caused it to breakdown relatively early compared to recent years. The metrics for the Antarctic ozone hole of 2012 showed some similarity with those of 1988 and 2002 (which were years of anomalously small ozone holes) despite all three years having distinctly different QBO indices indicating variant strengths of the polar vortex (and severity of ozone loss).